Analisis Pemanfaatan Layanan Book Delivery Pada Masa Endemi Covid-19 - Puspitadewi, Ganis Chandra; Hazrel, Annisa Wahyuni (JIPI (Jurnal Ilmu Perpustakaan dan Informasi), 2023)
The Universitas Nahdlatul Ulama Surabaya (UNUSA) book distribution service has seen a reduction as a result of library access, which was running smoothly during the Covid-19 prevalent period. This service, one of the best offered by the UNUSA library, is still provided, nonetheless. The purpose of this study is to learn how to use UNUSA's book delivery service. Descriptive qualitative research is used in this kind of study. Informants, research locations, and supporting documentation served as data sources. We used observation, documentation, and interviewing as our data collection methods. According to research conducted at the UNUSA library, books were borrowed and returned using the book delivery service by filling out information on a Google Form and paying with COD payment system. The performance of librarians shows a responsive, solutional, informative, and fast attitude in responding to requests for delivery of collections with delivery times of one day to three days with a shipping cost range of Rp.7000 – Rp.21000 depending on the distance of delivery and the delivery service used. Satisfaction with using the book delivery service shows the ease of users in accessing books so that they save more time and effort. However, access to book delivery services is quite difficult and users lack knowledge of the existence of these services, so it is necessary to evaluate book delivery services.Keywords: Library, Book delivery service, Covid-19 endemic, Nahdlatul Ulama University students in Surabaya